2019
DOI: 10.3390/sym11091113
|View full text |Cite
|
Sign up to set email alerts
|

Optical Helicity and Optical Chirality in Free Space and in the Presence of Matter

Abstract: The inherently weak nature of chiral light–matter interactions can be enhanced by orders of magnitude utilizing artificially-engineered nanophotonic structures. These structures enable high spatial concentration of electromagnetic fields with controlled helicity and chirality. However, the effective design and optimization of nanostructures requires defining physical observables which quantify the degree of electromagnetic helicity and chirality. In this perspective, we discuss optical helicity, optical chiral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 94 publications
1
86
0
Order By: Relevance
“…[39,43] Together with theories that can elegantly describe the interaction between chiral molecules and plasmonic nanostructures, [44][45][46][47] the study of chirality has entered a fast development path. There have been several reviews focusing on various aspects of this field, including fabrication, [39,43,48,49] theories, [50][51][52] and applications. [38,53,54] The goal of the present review, as illustrated in Scheme 1, is to elaborate the three physiochemical mechanisms of chirality transfer from sub-nanometer biochemical molecules to submicrometer metallic nanostructures, namely electromagnetic interaction induced chirality transfer, chiral assembly and chirality inheritance, molecular conformation change induced chirality.…”
Section: Introductionmentioning
confidence: 99%
“…[39,43] Together with theories that can elegantly describe the interaction between chiral molecules and plasmonic nanostructures, [44][45][46][47] the study of chirality has entered a fast development path. There have been several reviews focusing on various aspects of this field, including fabrication, [39,43,48,49] theories, [50][51][52] and applications. [38,53,54] The goal of the present review, as illustrated in Scheme 1, is to elaborate the three physiochemical mechanisms of chirality transfer from sub-nanometer biochemical molecules to submicrometer metallic nanostructures, namely electromagnetic interaction induced chirality transfer, chiral assembly and chirality inheritance, molecular conformation change induced chirality.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, for cylindrically symmetric particles, the absence of backscattered light follows from the preservation of EM helicity [14][15][16][17][18]. Conservation of helicity has proven crucial in many applications such as enhanced chiral light-matter interactions [19][20][21][22][23][24][25], or in the spin-orbit interactions of light [26][27][28][29][30][31][32]. In this vein, it has been reported that from a relatively simple far-field measurement of the EM helicity at a right angle, the radiation pattern of the dipolar particle is inferable [33].…”
mentioning
confidence: 99%
“…4(f), integrating the total contribution of entire SS yields no net energy transport along the bias field, as expected due to equilibrium conditions (see SI section B.2). Interestingly, analyzing the polarization state of each edge channel, we observe a well defined sign of the spatially-averaged opti-cal chiralityc > 0 [42][43][44][45][46][47] through the entire SS (see SI section B.3).…”
Section: Chiral Surface Statesmentioning
confidence: 98%